2014
DOI: 10.1002/app.40884
|View full text |Cite
|
Sign up to set email alerts
|

Observation on different reducing power of cocatalysts on the Ziegler–Natta catalyst containing alkoxide species for ethylene polymerization

Abstract: In this work, the effects of three types of cocatalyst having different alkyl groups, such as triethylaluminium (TEA), triisobutylaluminum (TiBA), and trioctylaluminium (TnOA), and their concentrations on the catalytic activity and polymer properties were investigated for the Ziegler–Natta catalyst containing alkoxide species. The drastic escalation of catalytic activity was observed when the ratio of Al/Ti was increased only for TEA because of its good diffusivity as proven by the electron spin resonance tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Finally, the reactor was pressurized with the total pressure of 8 bars with ethylene at 75°C. The polymerization time was 1 h. The obtained polymer was dried at room temperature overnight …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the reactor was pressurized with the total pressure of 8 bars with ethylene at 75°C. The polymerization time was 1 h. The obtained polymer was dried at room temperature overnight …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the g-value of 1.95 appeared to increase with the activation time indicating the presence of Ti 3+ ions. For quantitative analysis of Ti 3+ species, ESR peak area relating to the relative amounts with activation time of Ti 3+ species was calculated by double integration [15]. In addition, the ESR results obtained from Figure 1 were further calculated by double integration technique and normalized peak areas of interval time to compare with the data at initial time (no activation) to obtain the plot of relative area (corresponding to the amount of changes in Ti 3+ ) with time in Figure 2.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…They showed that TEA exhibited the highest activity and the activity enhanced with increased Al/Ti molar ratios (from 2 to 5). They concluded that an increase in Al/Ti molar ratios can alter the catalytic activity [15]. Later, other researchers suggested that different activators likely increased the insertion of 1-hexene in polyethylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The brown slurry mixture was observed. The catalyst slurry was purified by washing with n-hexane for seven times and dried under vacuum [82].…”
Section: Preparation Of Magnesium Powder Supported Catalystmentioning
confidence: 99%